Model Of Management Lubuk Larangan for Area Development in Mandailing Natal District - Putra, Erwin; ., Badaruddin; ., Rujiman; Saleh, Arifin (Journal of Ecohumanism, 2024)
This research proposes a comprehensive Model of Management for Lubuk Larangan, a unique cultural and natural resource in the Mandailing Natal District. Lubuk Larangan, traditionally known as a restricted fishing areas, holds significant cultural and ecological value for the local communities. However, the increasing pressures from modern development and anthropogenic activities necessitate the establishment of an effective management model to ensure sustainable area development.The proposed model integrates traditional wisdom, community participation, and modern management approaches to strike a balance between cultural preservation and sustainable development goals. It takes into account the socio-economic dynamics, environmental considerations, and aspirations of the local communities, aiming to create a harmonious and adaptive framework. Key components of the model include community engagement, knowledge transfer, regulatory frameworks, and monitoring systems. The model also emphasizes the importance of collaboration between local authorities, non-governmental organizations, and the communities to foster a sense of shared responsibility and ownership. This research utilizes quantitative methods approach quantitative data analysis to develop and validate the proposed model. The findings are expected to contribute to the sustainable development of Lubuk Larangan and serve as a valuable reference for similar initiatives in other regions facing the challenges of balancing cultural preservation and modern development. The model's success would not only benefit the Mandailing Natal District but also provide insights into the broader field of cultural and environmental resource management.